Macrofracturing of Oceanic Lithosphere in Complex Large Earthquake Sequences. Issue 10 (7th October 2020) - Lay, Thorne; Ye, Lingling; Wu, Zhenbo; Kanamori, Hiroo
Abstract: Major earthquakes in oceanic lithosphere seaward of the subduction zone outer trench slope are relatively uncommon, but several recent occurrences have involved very complex sequences rupturing multiple nonaligned faults and/or having high aftershock productivity with diffuse distribution. This includes the 21 December 2010 M W 7.4 Ogasawara (Bonin), 11 April 2012 M W 8.6 Indo‐Australia, 23 January 2018 M W 7.9 Off‐Kodiak Island, and 20 December 2018 M W 7.3 Nikol'skoye (northwest Pacific) earthquakes. Major oceanic intraplate event sequences farther from plate boundaries do not tend to be as complex in faulting or aftershocks. Outer trench slope extensional faulting can involve complex distributed sequences, particularly when activated by great megathrust ruptures such as 11 March 2011 M W 9.1 Tohoku and 15 November 2006 M W 8.3 Kuril Islands. Intense faulting sequences also occur near subduction zone corners, with many fault geometries being activated, including some in nearby oceanic lithosphere, as for the 29 September 2009 M W 8.1 Samoa, 6 February 2013 M W 8.0 Santa Cruz Islands, and 16 November 2000 M W 8.0 New Ireland earthquakes. The laterally varying plate boundary stresses from heterogeneous locking, recent earthquakes, or boundary geometry influence the specific faulting geometries activated in nearby major intraplate ruptures in oceanic lithosphere. Preexisting lithospheric structures and fabrics exert secondary influences on the faulting. Intraplate stress release in oceanic lithosphere near subduction zones favors distributed macrofracturing of near‐critical fault systems rather than localized, single‐fault failures, both under transient loading induced by plate boundary ruptures and under slow loading by tectonic motions and slab pull. Key Points: Major intraplate earthquake ruptures in oceanic lithosphere seaward of subduction zones have commonly involved multiple distributed faults The complex faulting has sometimes been accompanied by highly productive aftershock sequences with diversity in faulting mechanism Laterally or temporally varying plate boundary stress conditions concentrate intraplate stress gradients that drive the complex faulting